As condições de trabalho dos professores de ciências e as repercussões no seu trabalho pedagógico - Krützmann, Fábio Luis (2023)
Theorizing about teachers' working conditions is a central theme when thinking about school education for children and adolescents. Significant issue not only for education workers, but for society as a whole, since talking about education reverberates in our society. This research seeks to deepen the analysis of the repercussions of working conditions on the pedagogical work of science teachers. Given this, we propose to work with science teachers - Elementary School in the discipline of science and in High School in the disciplines of biology, physics and chemistry - studying the characteristics, singularities and conditions of these teachers. By aiming to understand the repercussions of working conditions on the pedagogical work of science teachers, we seek to help teachers in their reflections on the reality of work, as well as future research in the areas of science teaching and education. To achieve such a challenge, we found in Grounded Theory the methodological path rigorous enough to make a solid contribution and, at the same time, the necessary flexibility to face a complex and varied theme such as the working conditions of teachers. Semi-structured interview techniques and closed questionnaire created in the context of this research for application with teachers were used. Teachers who work in public and private schools in the state of Rio Grande do Sul participated in the research. By analyzing the data in the light of Grounded Theory, the following substantive theory was constructed: “the pedagogical work of science teachers is produced amidst a multitude of working conditions, which, in turn, are precarious and fragile, making it difficult to the construction of a pedagogical work coherent with its objectives and the needs of the students. The working conditions were identified as: insufficient and precarious work instruments, non-existent or insufficient planning time, the number of students and their difficulties making the process more complex, interferences and school contexts taking away the teachers' autonomy, overwork and relationships of employment and salary showing instability and devaluation. The result of this phenomenon is the widespread illness of teachers and the inability to renew and/or change the ongoing education”.